Die leksikografiese hantering van neo-klassieke en pseudo-sintaktiese komposita - van Niekerk, A.E. (Lexikos, 1991)
The Lexicographical Treatment of Neo-classical and Pseudo-syntactic Compounds The inconsistent treatment of neo-classical and pseudo-syntactic compounds in existing dictionaries can be ascribed mainly to uncertainty about the morphological status of these word-formations and to disregard for their status as compounds. Neo-classical compounds consist of a combination of a (usually) Greek or Latin word element and another element (affix or root). The Greek or Latin elements behave like affixes, but their ability to combine with affixes to form words calls into question their status as affixes. Moreover, the morphological and semantic differences between these elements and affixes are such that the elements could be referred to as neo-classical roots. The lexicographical treatment of the Greek and Latin word elements --- these can be Initial Combining Forms (ICFs) or Final Combining Forms (FCFs) --- is not based solely on linguistic considerations. For instance, in dictionaries such as the Verklarende Handwoordeboek van die Afrikaanse Taal (HAT) and the Nasionale Woordeboek (NW) the tendency to accord greater lexicographical prominence to initial roots in preference to final roots arises from the traditional word-based structure of dictionaries. Neo-classical roots should be included as sublexical items. The lexicographer should explain relationships in meaning to lexical variants by means of clear cross-references. Neither the HAT nor the NW are consistent in supplying etymological information for foreign word-elements, although this can have a useful encoding value to the dictionary user. Phonological information on variations in ICFs and accent-placement would also be helpful since this information is not readily predictable. In dealing with sublexical lemmas, the lexicographer should be consistent in the pattern of description, regardless of the status he wants to accord these elements. The lexicographer may neither ignore the productivity of neo-classical compounds, nor arbitrarily include or exclude them. As multi-worded lexical items, the pseudo-syntactic compounds form orthographical units as well as units of meaning. As single lexicon items such compounds qualify for inclusion in dictionaries. All rules applying to ordinary lexical items should be followed in the lexicographical treatment of pseudo-syntactic compounds. Thorough contextual guidance, well-considered cross-references and indications of number, which correspond with real language usage are indispensable. It is essential that the inclusion of multi-worded lexical items should be both semantically and lexicologically justified. The lexicographical processing of neo-classical and pseudo-syntactic compounds demands a more consistent and circumspect approach. Lexicographers should pay more careful attention to this in future.